2005
DOI: 10.3200/joer.99.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Parent Involvement and Mathematics Achievement: Contrast Across Racial and Ethnic Groups

Abstract: arent involvement, as a family educational input, has been advocated as a resource for school success in recent research and policy literature in the ABSTRACT The authors examined the relationships of 3 dimensions of parent involvement (family obligations, family norms, and parent information networks) to 12th-grade students' mathematics achievement and ways in which these relationships varied across 4 racial and ethnic groups (i.e., Caucasians, African Americans, Hispanics, and Asians). Using 4-year longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 62 publications
6
92
0
3
Order By: Relevance
“…The paper uses systematic review of literature to synthesize the correlation between parental involvement paradigms and positive learning outcomes in children. Although society and research evidence have long established a link between parents 'participation and students achievement (Barton & Coley, 2007;Horvat, Weininger, & Lareau, 2003;Sheldon & Epstein, 2005;Simon, 2004;Yan & Lin, 2005), evidence from other related studies reported little, if any, of such assessable effects (Bobbett, 1995;Mathews, 2005). Therefore, apart from individual goals and learners' beliefs, that have already been documented, variables like PI practice wield significant influence on learners' school achievement and behaviour.…”
Section: Purposementioning
confidence: 99%
“…The paper uses systematic review of literature to synthesize the correlation between parental involvement paradigms and positive learning outcomes in children. Although society and research evidence have long established a link between parents 'participation and students achievement (Barton & Coley, 2007;Horvat, Weininger, & Lareau, 2003;Sheldon & Epstein, 2005;Simon, 2004;Yan & Lin, 2005), evidence from other related studies reported little, if any, of such assessable effects (Bobbett, 1995;Mathews, 2005). Therefore, apart from individual goals and learners' beliefs, that have already been documented, variables like PI practice wield significant influence on learners' school achievement and behaviour.…”
Section: Purposementioning
confidence: 99%
“…A number of cross-cultural studies have sought to identify the factors influencing achievement, such as parental involvement factors (Yan & Lin, 2005) and schools' instructional practices (Shen, 2005). Further, studies have examined the influence of social-cognitive factors on school performance (Casey, Nuttall, & Pezaris, 2001;Ercikan, McCreith, & Lapointe, 2005;Leung, 2002), and the results have suggested that certain social cognitive factors are critical in influencing students' mathematics achievement.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the results of some research studies (Ushie, Emeka, Ononga, & Owolabi, 2012) do not support a causal relationship between single parenthood and school performance, thus emphasizing the inadequacy of the literature findings and indicating the importance and novelty of the present study. Among the factors that lead to decreased school performance in children who come from single-parent families are low academic expectations of lone parents (Shim, Felner, & Shim, 2000), lack of parental involvement in their children's education (Yan & Lin, 2005), low socio-economic status of the family (Amato & Keith, 1991), consequent stress of the lone parent to cope with the requirements of the new family patterns (Zinn, Eitzen, & Wells, 2008), poor quality of children's interpersonal relationships with both parents (Wallersetin & Kelly, 1975), time phase of the traumatic experience of separation/divorce (before, during or after divorce) (Tyber, 2011) and the supporting frame-assistance provided to single-parent family from parents, siblings, friends, family, school, state and other networks (Babalis, 2013). In the Greek area the study on the effect of single parenthood on behavior and school performance of students is fragmented, as the presence of such research is limited and focuses unilaterally on some dimensions of the issue (Babalis, 2011;Kogkidou, 2006;Xatzixristou, 2009).…”
Section: Introductionmentioning
confidence: 99%